Knowledge sharing between elementary teacher education students in online discussion - Safitri, Mazda Leva Okta; Fathurohman , Apit; Hermawan , Rudi; Suganda M , Vina Amilia (Universitas Ahmad Dahlan, 2023)
In online discussion activities, there are knowledge-sharing activities in which the factors are trust, equality, intrinsic motivation, and the use of technology. This type of research is descriptive quantitative. Here the researcher wants to explain the factors that influence knowledge-sharing activities among elementary teacher education students in online discussions. The sample of this study was 221 elementary teacher education students in Sumatra, Java, Kalimantan, and Sulawesi. Data analysis technique applied Multiple Linear Regression analysis techniques by using SPSS software version 21.0 with a significance level of 0.05. The results of this study indicated that similarity and technology use are factors that greatly influence knowledge-sharing activities, while trust and intrinsic motivation factors are factors that do not significantly affect knowledge-sharing activities. Equality factors such as age, background, and gender provide a major role in the success of knowledge-sharing activities. In order to support knowledge-sharing activities among elementary teacher education students to be effective and efficient, it is necessary to use technology with supportive frequency use.